Evaluation of facial expression recognition in patients with facial melasma: a cross-sectional study - França, Maria Laura Marconi [UNESP]; Miot, Hélio Amante [UNESP]; Schmitt, Juliano Vilaverde [UNESP]; Coutinho, Thales Vianna (GN1 Sistemas e Publicacoes, 2020)
Introduction: Melasma is frequent among women, and it is associated with a significant psychosocial impact. The facial expressions recognition is a cognitive process directly related to our emotional and psychosocial status. Objectives: This study evaluates the melasma patients' ability and healthy controls in identifying facial expressions reflecting six main emotions. Methods: This is a cross-sectional study, including 24 melasma patients and 24 healthy controls, matched for age. We collected demographic data, dermatology life quality index (DLQI), Hospital Anxiety and Depression Scale (HADS), and Social Phobia Inventory (SPIN). Also, we conducted a computerized facial emotion recognition test using 56 images. Results: The participants had a mean age of 39.8 (sd: 8.1), and the melasma patients reported a median of 84 months (p25-p75: 48-144) duration of the dermatosis and a median DLQI of 6 (2-10). Patients with melasma presented higher anxiety scores (9.4 [4] x 6.7 [4.3]; p=0.03) and showed higher accuracy in identifying emotions due to their greater success in recognizingfear (35 [13-52] x 13 [3-25]; p=0.03). The non-biased right answers' difference remained significant after multivariate analysis adjusted for the anxiety scores (p<0.01). Conclusions: Women with melasma presented a higher accuracy in recognizing facial expressions of fear, suggesting differentiated brain processing of emotions in this population.
Avaliação do reconhecimento das expressões faciais em pacientes com melasma facial: um estudo transversal
Keywords: Anxiety; Emotions; Melanosis